Gram-negative bacterial sRNAs encapsulated in OMVs: an emerging class of therapeutic targets in diseases - Ajam-Hosseini, Mobarakeh; Akhoondi, Fatemeh; Parvini, Farshid; Fahimi, Hossein (Frontiers in Cellular and Infection Microbiology, 2024)
Small regulatory RNAs (sRNAs) encapsulated in outer membrane vesicles (OMVs) are critical post-transcriptional regulators of gene expression in prokaryotic and eukaryotic organisms. OMVs are small spherical structures released by Gram-negative bacteria that serve as important vehicles for intercellular communication and can also play an important role in bacterial virulence and hostpathogen interactions. These molecules can interact with mRNAs or proteins and affect various cellular functions and physiological processes in the producing bacteria. This review aims to provide insight into the current understanding of sRNA localization to OMVs in Gram-negative bacteria and highlights the identification, characterization and functional implications of these encapsulated sRNAs. By examining the research gaps in this field, we aim to inspire further exploration and progress in investigating the potential therapeutic applications of OMVencapsulated sRNAs in various diseases.